Electrocardiographic changes in dogs with Mitral Valve Disease - Sindhu K Rajan; Narayana Pillai, Usha; S, Ajithkumar (Indian Journal of Veterinary Medicine, 2025)
Mitral valvular disease is the most common acquired cardiac disease in dogs, which is characterised grossly by nodular distortion of the valve leaflets, as well as by thickening and lengthening of the chordae tendineae. The electrocardiogram is an insensitive gauge of cardiac chamber size. The diagnosis of mitral valve disease is difficult in field conditions especially in non sophisticated hospitals. The study was conducted in six dogs with mitral valve disease. Dogs brought to general health check up and vaccination were selected as the control animals. Confirmation of mitral valve disease was carried out using echocardiography. Fine atrial fibrillation was the major electrocardiographic findings in dogs diagnosed with mitral valvular disease. Even though, no statistical significance could be established between control and diseased dogs, duration of P wave, QRS, PR, ST and QT interval were increased in diseased dogs. The present study aids in the diagnosis of dogs with mitral valve disease with the help of electrocardiography.